Floristic characteristics and diversity of east asian plants - Aoluo, Z.; Sugong, W. (eds.) (Beijing China Higher Education Press & Springer Verlag, 1998)
Congresos
Proceedings of the First Int. Symposium on Floristic Characteristics and Diversity of East Asian Plants July 25-27, 1996. Kunming, Yunnan, P. R. China
Keywords: Flora; China